Pengembangan Media Pembelajaran E-Comic Berbasis Problem Based Learning dalam Muatan Pelajaran Bahasa Indonesia Materi Teks Iklan Kelas V SD - Putu Mita kesuma Dewi; Ni Nyoman Ganing; I Wayan Sujana (Universitas Pahlawan Tuanku Tambusai, 2022)
This research is motivated by the lack of understanding of students in Indonesian subjects due to the lack of variety of learning media along with the learning models used by teachers during the learning process. This study aims to describe the design and development of problem-based learning E-Comic learning media and analyze the validity of problem-based learning E-Comic learning media. This research uses the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model type. The subjects of this research trial were 1 design expert, 1 learning content expert, 1 instructional design expert, 1 learning media expert, 3 individual trial people, and 9 small group trial people. The data collection method used in this study was a questionnaire or questionnaire with quantitative descriptive data analysis techniques. The research results (a) the learning media design obtained a percentage score of 100.00% (very good), (b) the validity results of the development of E-Comic learning media from content experts obtained a percentage score of 95.00% (very good), design experts obtained a percentage score of 95.00% (very good), media experts obtained a percentage score of 97.90% (very good), individual trials obtained a percentage score of 96.66% (very good), and small group trials obtained a percentage score of 96.94% (very good). So it can be concluded that problem-based E-Comic learning media in lesson content Indonesian advertising text materials are suitable for use in grade V elementary schools.